PENGEMBANGAN MEDIA DIGIBUK BERBASIS IMAGINATIVE NARRATIVE GAMES UNTUK MENINGKATKAN KREATIVITAS SISWA SD MATERI POLA LANTAI - Anisa Wulan Suci Rahmawati; Deasylina da Ary (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study aims to develop, test the feasibility, and effectiveness of DIGIBUK media based on imaginative narrative games in an effort to increase creativity in floor pattern material for grade V elementary school students. The type of research used is Research and Development (R&D), which is adapted from the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this research include material experts and learning media experts. The test subjects were teachers and grade V elementary school students, as many as 27 people. The data collection techniques include observation, interviews, questionnaires, and tests. The instruments used to collect data include observation sheets, interview guidelines, needs questionnaires, validation questionnaires, response questionnaires, and test questions. The DIGIBUK product was developed based on the needs analysis results of students who showed interest in movement activities, stories, and imaginative approaches. This media consists of three main menus: floor pattern material, imaginative narrative games, and practical evaluation. The feasibility test results showed that DIGIBUK scored 94.28% from the material expert and 96.66% from the media expert, with very feasible criteria. The effectiveness test using the t-test showed a significance value of 0.000 <0.05 and an N-Gain value of 0.71, which is included in the high category. Thus, the development of DIGIBUK media is declared feasible and effective to increase student creativity in learning dance, especially in floor pattern material, through an imaginative narrative game approach.